Penerapan Model Pembelajaran Role Playing Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas V Sekolah Dasar - Jennej J. Rawung; Risal M. Merentek (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to improve the learning outcomes of the fifth graders of elementary school Indonesian. This research activity was carried out at Kombi State Elementary School. This activity was carried out using the classroom action research method. Classroom action research activities according to Kemmis and McTaggart's instructions consist of four components: 1) planning, 2) action, 3) observation, 4) reflection, using a spiral model. Based on the results of the study, it can be said that the application of the Role Playing learning model can improve teacher performance in the implementation of learning to write simple dialogue texts. Where the achievement of learning outcomes in cycle 1 is only 60.2% has not reached the minimum completeness criteria value, and increased in cycle 2 to reach 80.6% has reached the minimum completeness criteria value. Improving the way teachers in carrying out the learning process is able to improve student learning outcomes. Increase student activity in learning.